Genetics, genomics and breeding of eucalypts - Henry, Robert J.; Kole, Chittaranjan (Genetics, genomics and breeding of crop plants., 2015)
Eucalypts are used for the production of paper products, firewood, charcoal, potential feedstocks for bioenergy and biomaterials, as ornamentals and landscape trees, and in land rehabilitation. Eucalypt breeding is at an early stage with many plantings being only at the first stages of domestication. The relatively small genomes of these species make the application of molecular genetics approaches attractive. The application of modern genomics will accelerate the development of improved eucalypts for a wide range of uses. This book brings together diverse information on the genetics, genomics.